The Use of Tag Questions in the Academic Context - Haque, Muhammed Shahriar (2002)
According to Lakoff (1975), tag questions are a feature of what she calls "women's language" and that women use them more than men. However studies conducted as a result of her claim show inconsistent findings. Many authorities on the subject such as Holmes (1984,1995), Coates and Cameron (1989), Dubois and Crouch (1975) are of the opinion that the use of tag questions is dependent on many linguistic and extra-linguistic factors and not merely gender. Studies on the use of tag questions have been conducted in various contexts and situations but not specifically in the academic context at the tertiary level in Malaysia. In light of the relatively limited information that is available regarding the use of tag questions in the academic context, the nature of the study is descriptive and exploratory. The study adopts a quantitative as well as a qualitative design. The study sample was made up of lecturers and students from the English Departments of Universiti Putra Malaysia, International Islamic University Malaysia and Tunku Abdul Rahman College. The data was collected by means of questionnaire and audiotape recordings of lectures and oral presentations. The findings suggest that in the academic arena, both men and women use different forms of tag questions, with women using them slightly or marginally more than men. The most frequently used tag questions are the comformative, responsive and information seeking types, which function to request the agreement of the audience, to invite response from the audience and to express uncertainty respectively. Speakers usually feel that the use of tag questions boosts their level of confidence and creates a congenial atmosphere for interaction to take place. The study also revealed that a single category of question tag could function as different forms of tag questions and vice versa. In the Malaysian academic context the most frequently used linguistic realizations of question tag categories by both genders are OK and all right. This study sheds some light on the use of tag questions in the academic context. The findings of this study may help later studies to explore whether the use of tag question is dependent on factors such as different contexts, situations, intentions, cultures and varieties of English.